2017
DOI: 10.3389/fpsyg.2017.00135
|View full text |Cite
|
Sign up to set email alerts
|

Suppression Benefits Boys in Taiwan: The Relation between Gender, Emotional Regulation Strategy, and Mental Health

Abstract: Emotion regulation (ER) strategies have a clear impact on mental health outcomes. In 2 studies (N = 695, N = 433) we investigated gender differences in the use of 2 ER strategies (reappraisal and suppression) to handle parent-child conflict in Taiwanese adolescents. We also identified the implications of these differences for some negative emotions (self-blame and resentment) and internalizing problems (psychosomatic symptoms and social withdrawal). Results of the correlation analyses in both studies indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
1
27
0
1
Order By: Relevance
“…In this case, both expressive suppression and cognitive reappraisal may be common approaches of emotion regulation in the Chinese context. Consistent with prior studies on emotion regulation in Asian youth (Chen et al, 2020 ; Yeh et al, 2017 ), the current study found that expressive suppression was positively correlated with cognitive reappraisal. Moreover, past research suggests that expressive suppression may be less harmful to psychological well-being in the Chinese cultural context compared to in the Western cultural context (Soto et al, 2011 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this case, both expressive suppression and cognitive reappraisal may be common approaches of emotion regulation in the Chinese context. Consistent with prior studies on emotion regulation in Asian youth (Chen et al, 2020 ; Yeh et al, 2017 ), the current study found that expressive suppression was positively correlated with cognitive reappraisal. Moreover, past research suggests that expressive suppression may be less harmful to psychological well-being in the Chinese cultural context compared to in the Western cultural context (Soto et al, 2011 ).…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that compared with girls, boys are less inclined to seek social support and use effective emotional regulation strategies and they are more likely to suppress or avoid emotional expression ( Gross and John, 2003 ; Nolen-Hoeksema, 2012 ). This is particularly the case in Chinese contexts where boys are socialized to be tough and emotionally suppressive while girls are encouraged to be more sensitive ( Yeh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…An individual may need to regulate the expression of emotions for a multitude of reasons such as: to comply to the social norms of a situation and adhere to display rules (not laughing at the teacher); to avoid others knowing what one actually feels (not showing a bully you are afraid); to help someone else to regulate his/her emotions (not showing one's anxiety to a younger sibling in a potentially dangerous situation). Broadly speaking, it is likely that the degree of adaptive expression of one's emotions varies greatly across different situations, relationships and cultures (Cole, Bruschi & Tamang, 2002;English et al, 2016;Yeh, Bedford, Wu, Wang & Yen, 2017).…”
Section: Discussionmentioning
confidence: 99%